2016
DOI: 10.1097/md.0000000000005701
|View full text |Cite
|
Sign up to set email alerts
|

Combined adductor canal block with periarticular infiltration versus periarticular infiltration for analgesia after total knee arthroplasty

Abstract: Background:Both adductor canal block (ACB) and periarticular infiltration (PI) have been shown to reduce pain after total knee arthroplasty (TKA) without the motor blockade. However, the efficacy and safety of combined ACB with PI (ACB + PI) as compared to PI alone for analgesia after TKA remains controversial. We therefore performed a meta-analysis to compare the effects of ACB + PI with PI alone on pain controll after TKA.Methods:PubMed, Medline, Embase, Web of Science, and the Cochrane Library were searched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 27 publications
3
21
1
Order By: Relevance
“…The pooled results indicated that ACB combined LIA was associated with a less pain scores at 24 h and 48 h after TKA, which was equivalent on a 110-point VAS to 7.42 points at 24 h and 4.72 points at 48 h. Ma et al [17] conducted a meta-analysis about the combined ACB with periarticular infiltration versus periarticular infiltration for analgesia after TKA. The results of their meta-analysis revealed that combined ACB with periarticular infiltration may not associate with a reduction in analgesia when compared to periarticular infiltration alone in the early postoperative period after TKA.…”
Section: Discussionmentioning
confidence: 99%
“…The pooled results indicated that ACB combined LIA was associated with a less pain scores at 24 h and 48 h after TKA, which was equivalent on a 110-point VAS to 7.42 points at 24 h and 4.72 points at 48 h. Ma et al [17] conducted a meta-analysis about the combined ACB with periarticular infiltration versus periarticular infiltration for analgesia after TKA. The results of their meta-analysis revealed that combined ACB with periarticular infiltration may not associate with a reduction in analgesia when compared to periarticular infiltration alone in the early postoperative period after TKA.…”
Section: Discussionmentioning
confidence: 99%
“…Although different analgesic techniques have been used for total knee arthroplasty such as epidural anaesthesia, FNB, ACB, intra-articular local anaesthetic infiltration, or systemic analgesia, there is no consensus on the ideal approach. FNB is a well-established technique, and was considered the standard of postoperative analgesia in TKA [3]. Recent studies have compared FNB to PCA regimens or other nerve block techniques demonstrating the analgesic utility of FNB in total knee arthroplasty, but also its association with quadriceps muscle weakness, delayed ambulation, and a risk of falling [4,5].…”
Section: Discussionmentioning
confidence: 99%
“…Although various analgesic techniques have been proposed, there is currently no consensus on the optimal protocol to improve functional outcomes following total knee arthroplasty. The ideal analgesic regimen should enable early ambulation and physical therapy, shorten hospital stay, reduce the risk of postoperative complications and improve patient satisfaction [3]. Ultrasoundguided femoral nerve block (FNB) is one of the most commonly used techniques that has been shown to significantly improve analgesia and reduce postoperative opioid consumption.…”
Section: Introductionmentioning
confidence: 99%
“… 2 Recent research has indicated that ACB in combination with LIA may achieve satisfactory effects, as well as an improved functional outcome. 4 , 10 …”
Section: Introductionmentioning
confidence: 99%